2013
DOI: 10.3945/jn.113.179564
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors Influence Production of the Soy Isoflavone Metabolite S-(-)Equol in Healthy Adults

Abstract: S-(-)equol, an intestinally derived metabolite of the soy isoflavone daidzein, is proposed to enhance the efficacy of soy diets. Adults differ in their ability to produce equol when consuming soy foods for reasons that remain unclear. Therefore, we performed a comprehensive dietary analysis of 143 macro- and micronutrients in 159 healthy adults in the United States (n = 89) and Australia (n = 70) to determine whether the intake of specific nutrients favors equol production. Three-d diet records were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 65 publications
2
34
0
1
Order By: Relevance
“…Setchell stated that duration and amount of daidzein-containing food, type of intestinal microbiota population, such as bacteria with ability to reduce sulfa, amount of polyunsaturated fatty acid, and vitamin A and E in food influenced level of equol in vivo. Elimination of equol within plasma was 7-8 hrs [28]. This may be the reason the previous studies conducted "challenge" by giving soycontaining food prior examining respondent's equol level just to be assessed by urine collection or blood withdraw.…”
Section: Discussionmentioning
confidence: 99%
“…Setchell stated that duration and amount of daidzein-containing food, type of intestinal microbiota population, such as bacteria with ability to reduce sulfa, amount of polyunsaturated fatty acid, and vitamin A and E in food influenced level of equol in vivo. Elimination of equol within plasma was 7-8 hrs [28]. This may be the reason the previous studies conducted "challenge" by giving soycontaining food prior examining respondent's equol level just to be assessed by urine collection or blood withdraw.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-day diet records were analyzed using the Nutrition Data System for Research software (Nutrition Coordinating Center, University of Minnesota, Minneapolis, MN, USA), as described previously [29,30]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in our study, equol was assessed at only one time point. Although equol production has been shown to be relatively stable within individuals over time in some studies [42, 43], others have suggested that around 6 to 20% of individuals vary or crossover equol phenotypes over relatively short periods of time [44, 45]. However, the evidence to date suggests there is more often a producer to non-producer shift than vice versa [4245].…”
Section: Discussionmentioning
confidence: 99%